2011
DOI: 10.3109/00365521.2010.545831
|View full text |Cite
|
Sign up to set email alerts
|

Malignant gastroduodenal obstruction: Retrospective comparison of endoscopic and surgical palliative therapy

Abstract: In this study, ES is a generally equivalent--and in several points superior--alternative to GE for palliation of malignant gastroduodenal obstruction. ES seems to be the less invasive alternative for symptomatic patients. GE has good results in patients with longer survival and can be practiced within abdominal explorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
0
22
0
2
Order By: Relevance
“…Stented patients had fewer complications, faster return to oral intake, and shorter hospitalizations. [39–42] However, the surgical gastrojejunostomy or endoscopic stent placement for the palliation of malignant gastric outlet obstruction (SUSTENT) trial, a multicenter randomized control trial comparing stenting to surgery, found that although endoscopic palliation showed a quicker return to oral intake (5 vs. 8 days) at 30 and 60 days, the surgical group had significantly better oral intake. After adjusting for survival, surgery was associated with more total days tolerating oral intake and is recommended for patients with a life expectancy of 2 months or longer.…”
Section: Gastric Outlet Obstructionmentioning
confidence: 99%
“…Stented patients had fewer complications, faster return to oral intake, and shorter hospitalizations. [39–42] However, the surgical gastrojejunostomy or endoscopic stent placement for the palliation of malignant gastric outlet obstruction (SUSTENT) trial, a multicenter randomized control trial comparing stenting to surgery, found that although endoscopic palliation showed a quicker return to oral intake (5 vs. 8 days) at 30 and 60 days, the surgical group had significantly better oral intake. After adjusting for survival, surgery was associated with more total days tolerating oral intake and is recommended for patients with a life expectancy of 2 months or longer.…”
Section: Gastric Outlet Obstructionmentioning
confidence: 99%
“…Interesting clinical data were presented from a German group, looking at the relative utility of surgical versus endoscopic resolution of malignant gastric outlet obstruction [4]. They did a retrospective non-controlled comparison of surgical gastroenterostomy to endoscopic placement of a self-expanding stent and showed that results were largely comparable, but with a less invasive approach and a quicker postoperative recovery favoring endoscopy.…”
Section: Editorialmentioning
confidence: 98%
“…In the past, surgical bypasses (biliary-digestive and gastro-jejunal anastomoses) were used for palliative treatment of biliary or duodenal obstruction, but currently endoscopic stenting is the preferred method. In the literature, several studies have compared the endoscopic and surgical palliative treatment of jaundice or duodenal obstruction in patients with unresectable PC [216][217][218][219][220][221][222][223]. The summary results show an advantage to endoscopic treatment in terms of quality of life, duration of hospitalization, and cost.…”
Section: Endoscopic Therapy In Biliary/duodenal Obstructionmentioning
confidence: 99%
“…The results of meta-analysis by the Cochrane Collaboration showed that rate of technical success and short-term efficacy in comparison of palliative endoscopic biliary drainage and surgical drainage for obstructing pancreatic carcinoma were similar, but the morbidity and duration of hospitalization are higher for surgical bypass [217,218]. It was reported by various authors that endoscopic treatment of duodenal stenosis compared to bypass surgery was related with fewer complications, shorter hospitalization, and lower cost [219][220][221][222][223].…”
Section: Endoscopic Therapy In Biliary/duodenal Obstructionmentioning
confidence: 99%
See 1 more Smart Citation